Student views of the relevance of learning English at secondary school - Jeeves, Anna (Milli Mála, 2022)
The qualitative study explores perceptions of English as a compulsory subject at secondary school in Iceland, a country rich in exposure to English. Interviews were taken in Icelandic with students at secondary school and university and with young people in employment. Analysis was based on phenomenology and grounded theory research. Data show that many teenagers evaluate their competence in English as very good and sufficient for university study and work. Many respondents see English as an easy subject; some see their learninggains at secondary school as minimal. Many respondents at university report having anticipated using English in their studies and value secondary school English classes. Secondary school English appears to have less benefit for young people starting work straight after school. With the exception of those who learned domain-specific vocabulary in vocational courses, they find themselves using English at work in different ways than they expected. The significance of the study for secondary school teachers is discussed, and suggestions made forteaching to focus more on the future language needs of students. The importance of student-teacher discussion of curriculum material, aims, relevance and assignments, is also emphasized.Keywords: English; relevance; students; views; gains Tekin voru djúp viðtöl við framhaldsskóla- og háskólanema og við ungt fólk í vinnu til að kanna viðhorf til enskunáms í framhaldsskóla á Íslandi. Rannsóknin byggist á hugsmíðahyggju og túlkunarfyrirbærafræði. Margir ungir Íslendingar notast mikið við ensku í daglegu lífi, enda er flest afþreyingarefni sem þeir neyta á ensku. Niðurstöður sýna að margir ungir Íslendingar telja færni sína í enskumjög góða. Enskunám er talið vera létt og góðar einkunnir auðfengnar. Háskólanemar kunna að meta framhaldsskólaáfanga í ensku og þeir hafa gert ráð fyrir að þurfa að nota ensku í háskólanámi sínu. Viðmælendur sem fóru strax út á vinnumarkaðinn eftir framhaldsskóla nota ensku meira í vinnunni en þeir gerðu ráð fyrir og telja ...